PENGARUH PENAMBAHAN TEPUNG DAUN PEPAYA (CARICA PAPAYA L) TERHADAP PERFORMA AYAM BROILER - Pratama, Singgih; Sariri, Ahimsa Kandi (Universitas Islam Balitar, 2025)
This study looks into how using papaya leaf flour affects broiler chicken performance. In the study, 48 broiler chicks without sexes were given treatments ranging from 0% to 9% papaya leaf flour. comprises three broiler birds in each of the four replications. Among the traits assessed feed consumption, growth rate, and ration efficiency. The Analysis of Variance (ANOVA) approach employed to interpret research findings. Additionally, the average difference for each therapy was examined using Duncan’s range comparison test. Study outcomes showed show that papaya leaf flour significantly affects feed consumption but has no effect on feed conversion or body weight gain.